Development of graphical user interface (GUI) for surgery assistance application - Mardhiyah Md Jan,; Nasharuddin Zainal,; Siti Hajar Yusof, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Telemedicine is a technology that promotes patient engagement and makes healthcare more affordable and accessible. Telehealth technologies are used in healthcare settings such as teleconferencing, patient data transfer, and shared remote learning. However, current teleconferencing has limited ability to perform annotation on real-time videos. The proposed surgery assistance system would revolutionize the medical surgery industries where surgery can be monitored remotely by a surgical specialist with minimal assistance. The supervising surgeon can provide assistance to his subordinates in the operating room by annotating on videos of body parts transmitted live then the annotation will be projected directly onto the patient’s body as physician’s guidance. A comprehensive surgery assistance system is proposed as there are not many open-source systems that can support this technology. The system is capable of detecting the reference points placed on the body parts that will be operated on. Any movement of the reference points should be detected by this system, which would also alert the user with a message when movement is detected. This process is critical to ensure that the video images delivered to the remote monitor are identical to the video images captured in the operating room. Python version 3.9.4 was used, along with its associated libraries, to develop the proposed system. Socket communication using Transport Control Protocol (TCP) is used to make video transmission more secure. The proposed graphical user interface was accessed experimentally using the functional and reliability tests with the average percentage of 92% and 95% respectively to ensure that it was well implemented and both of the proposed goals were achieved.